Toxic dinoflagellate blooms of Gymnodinium catenatum and their cysts in Taiwan Strait and their relationship to global populations - Liu, Minlu; Gu, Haifeng; Krock, Bernd; Luo, Zhaohe; Zhang, Yubo (Harmful algae, 2020)
•Gymnodinium catenatum blooms occurred in the Taiwan Strait in 2017 and 2018.•Gymnodinium catenatum cyst density increased markedly after the bloom in 2017.•Gymnodinium catenatum population in the Taiwan Strait belongs to a warm water ecotype.•Gymnodinium catenatum in the Taiwan Strait has a unique paralytic shellfish toxin profile. Gymnodinium catenatum is able to produce paralytic shellfish toxins (PSTs) and was responsible for a massive bloom in the Taiwan Strait, East China Sea, in June 2017, which resulted in serious human poisoning and economic losses. To understand the origin of the bloom and determine the potential for blooms in subsequent years, water and sediment samples collected in the Taiwan Strait from 2016 to 2019 were analyzed for cells and cysts using light microscopy (LM) and/or quantitative polymerase chain reaction (qPCR). The morphology of both cells and cysts from the field and cultures was examined with LM and scanning electron microscopy (SEM). Large subunit (LSU) and/or internal transcribed spacer (ITS)-5.8S rRNA gene sequences were obtained in 13 isolates from bloom samples and five strains from cysts. In addition, cells of strains TIO523 and GCLY02 (from the Taiwan Strait and Yellow Sea of China, respectively) were subjected to growth experiments, and cysts from the field were used for germination experiments under various temperatures. Our strains shared identical LSU and ITS-5.8S rRNA gene sequences with those from other parts of the world, and therefore belonged to a global population. A low abundance of G. catenatum cells were detected during most of the sampling period, but a small bloom was encountered in Quanzhou on June 8, 2018. Few cysts were observed in 2016 but a marked increase was observed after the bloom in 2017, with a highest density of 689 cysts cm−3. Cysts germinated at temperatures between 14 and 23 °C with a final germination rate over 93%. Strains TIO523 and GCLY02 displayed growth at temperatures between 17 and 26 °C and 14 and 26 °C, respectively, with both strains displaying the highest growth rate of ca. 0.5 divisions d–1 at 23 °C. The PSTs of the three strains and cysts from the sediments were analyzed by liquid chromatography with tandem mass spectrometry (LC-MS/MS). All strains were able to produce PSTs, which were dominated by N-sulfocarbamoyl C toxins (C1/2, 53.0–143.5 pg cell−1) and decarbamoyl gonyautoxins (dcGTX2/3, 26.7–52.1 pg cell−1), although they were not detected in cysts. However, hydroxybenzoyl (GC) toxins were detected in both cells and cysts. Our results suggested that the population in the Taiwan Strait belonged to a warm water ecotype and has a unique toxin profile. Our results also suggested that the persistence of cells in the water column may have initiated the bloom.